Attendance in Class and Motivation to Study in an Engineering Course: Exploring their Associations and Gender Differences - Unissa, Azeem; Nagabhushan, Prathiba (Journal of Engineering Education Transformations, 2025)
There is an increasing evidence for associations between students' attendance and their academic achievement in general. However, it is not clear how it is related to students' motivational behaviours such as, study planning and management, especially in the context of engineering education. This study examines this relationship on a sample of engineering students (N=98). The results showed a significant positive relationship between student attendance and study management and between study planning and study management behaviours. Significant gender differences revealed that female students reported higher levels of attendance and study management behaviours than male students. Further research is required to pursue this initial understanding of motivational orientations of engineering students by tracking their attendance and motivational behaviours over time. Limitations of the current study are discussed and recommendations for future research are presented.